2019
DOI: 10.1111/jpc.14593
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum hepcidin levels in children with inflammatory bowel disease during anti‐inflammatory treatment

Abstract: Aim The aim of this study was to compare changes in serum hepcidin levels in paediatric patients with inflammatory bowel disease during therapy and correlate them with markers of iron metabolism, inflammation and type of treatment. Methods Children with newly diagnosed Crohn's disease (CD) and ulcerative colitis (UC) were included in this longitudinal study. Blood and stool samples were collected to assess levels of serum hepcidin and markers of iron metabolism parameters and inflammation. The parameters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…Karaskova et al (25) also demonstrated that in pediatric IBD patients the level of IL-6 decreased after treatment. Our study results about IL-6 were parallel to the findings of pediatric and adult studies in literature (24,25).…”
Section: Discussionsupporting
confidence: 90%
“…Karaskova et al (25) also demonstrated that in pediatric IBD patients the level of IL-6 decreased after treatment. Our study results about IL-6 were parallel to the findings of pediatric and adult studies in literature (24,25).…”
Section: Discussionsupporting
confidence: 90%
“…This decrease was significant in patients who responded to the treatment compared with those who did not. 30 , 32 , 38 , 39 Likewise, these trends were observed in other patient populations (eg, in patients with rheumatoid arthritis). 40 Because most iron indices are also acute-phase proteins (ie, inflammation increases ferritin and decreases transferrin), previous data and our findings suggest that appropriate anti-inflammatory treatment during phases of active IBD can reduce hepcidin levels and, consequently, might improve the bioavailability of iron supplements.…”
Section: Discussionsupporting
confidence: 61%
“…IL-6 increases gene transcription of hepcidin and decreases the gene expression of ferroportin and therefore decreases intestinal iron absorption. 21 , 22 …”
Section: Discussionmentioning
confidence: 99%